Alcohol-Activated Vanadium-Containing Polyoxometalate Complexes in Homogeneous Glucose Oxidation Identified with 51V-NMR and EPR Spectroscopy - Wesinger, Stefanie; Mendt, Matthias; Albert, Jakob (ChemCatChem, 2021)
Alcoholic solvents, especially methanol, show an activating affect for heteropolyacids in homogenously catalysed glucose transformation reactions. In detail, they manipulate the polyoxometalate-based catalyst in a way that thermodynamically favoured total oxidation to CO2 can be completely supressed. This allows a nearly 100 % carbon efficiency in the transformation reaction of glucose to methyl formate in methanolic solution at mild reaction conditions of 90 °C and 20 bar oxygen pressure. By using powerful spectroscopic tools like 51V-NMR and continuous wave EPR we could unambiguously prove that the vanadate-methanol-complex[VO(OMe)3]n is responsible for the selectivity shift in methanolic solution compared to the aqueous reference system.
CRIS-Team Scopus Importer:2021-06-25
Keywords: EPR spectroscopy; Keggin polyoxometalates; NMR spectroscopy; solvent effect; vanadium redox chemistry

Combining autoclave and LCWM reactor studies to shed light on the kinetics of glucose oxidation catalyzed by doped molybdenum-based heteropoly acids - Voß, Dorothea; Ponce, Sebastian; Wesinger, Stefanie; Etzold, Bastian J.M.; Albert, Jakob (RSC Advances, 2019)
In this work we combined kinetic studies for aqueous-phase glucose oxidation in a high-pressure autoclave setup with catalyst reoxidation studies in a liquid-core waveguide membrane reactor. Hereby, we investigated the influence of Nb- and Ta-doping on Mo-based Keggin-polyoxometalates for both reaction steps independently. Most importantly, we could demonstrate a significant increase of glucose oxidation kinetics by Ta- and especially Nb-doping by factors of 1.1 and 1.5 compared to the classical HPA-Mo. Moreover, activation energies for the substrate oxidation step could be significantly reduced from around 80 kJ mol-1 for the classical HPA-Mo to 61 kJ mol-1 for the Ta- and 55 kJ mol-1 for the Nb-doped species, respectively. Regarding catalyst reoxidation kinetics, the doping did not show significant differences between the different catalysts.
CRIS-Team Scopus Importer:2019-10-01

Sensitivity Analysis and Parameter Optimization for the Fractionative Catalytic Conversion of Lignocellulosic Biomass in the Polyoxometalate-lonosolv Concept - Bukowski, Anna; Schnepf, Kristin; Wesinger, Stefanie; Brandt-Talbot, Agnieszka; Albert, Jakob (ACS Sustainable Chemistry & Engineering, 2022)
The recently developed polyoxometalate (POM)-ionosolv concept offers an interesting strategy to generate two valuable product streams from lignocellulosic biomass, a solid cellulose-rich pulp and short-chain carboxylic acids like formic acid and acetic acid in a simple and cost-efficient manner. This study aimed to find optimum parameters for the two steps of the transformation by performing a sensitivity analysis on the initial ionosolv fractionation step as well as kinetic investigations of the following POM-catalyzed oxidation step. The results were transferred to the POM-ionosolv concept to find the overall process optimum. Beech wood was used as an industrially relevant substrate for ionosolv fractionation with the low-cost ionic liquid triethylammonium sulfate, [TEA][HSO4], and the HPA-5 [H8PV5Mo7O40] POM catalyst for the oxidation of the dissolved components in an oxygen atmosphere. As the most seminal finding, we defined optimum conditions of 125 degrees C, 1200 rpm, 30 bar oxygen, and 24 h reaction time in ionic liquid containing 70% water, achieving 72% xylose extraction from beech wood, which resulted in a 39% formic acid yield. We suggest that the fractionation and catalytic conversion are carried out at different water contents for maximum conversion efficiency for each step.
CRIS-Team WoS Importer:2022-07-08
Keywords: Lignocellulose; Fractionation; Ionic liquid; Polyoxometalate; Formic acid; Cellulose